MODEL ADAPTABILITAS ORGANISASI DAN KEUNGGULAN BERSAING MELALUI KOLABORASI VIRTUAL, TRANSDISIPLINARITAS, KETRAMPILAN KOMPUTASIONAL DAN KOMPETENSI BUDAYA - Pujo Sugito; Kamaludin Kamaludin (Jurnal Manajemen dan Kewirausahaan, 2016)
The aim of this research is to contruct a model of organizational adaptability and competitive advantage: a virtual collaborative approach, transdisiplinaritas, computational skills and cross-cultural competence. A new competitive advantage model that can enrich the science of management, especially in management strategy contex. The research population are all small and medium enterprises in Malang, amounting to 279,103 units (the Department of Cooperatives and SMEs, 2015). The data collection technique is proportional random sampling a sample unit is selected based on a certain proportion in order to meet samples with specific characteristics. The respondents number in this study determined 100 respondents. The primary data will be analyzed by :1) factor analysis, 2) regression weight on SEM, and 3) discriminant analysis. Furthermore, SEM modeling through a) developing the model, b) making path diagram, c) selecting input matrix and estimating the model, d) evaluating criteria of goodness-of-fit, and e) interpreting and modifying the model. Based on the results of data analysis revealed that the virtual collaborative approach, transdisiplinaritas, computational skills and cross-cultural competence a significant effect on the competitive advantage, either directly or indirectly through the variable organizational adaptability. Even, the findings of the trial results support the adaptability of the theoretical model.